2022
DOI: 10.21203/rs.3.rs-2002501/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First non-covalent inhibitors of thioredoxin glutathione reductase with schistosomicidal activity in vivo

Abstract: Only one drug, praziquantel, is available for treating schistosomiasis, a disease affecting more than 200 million people. Laboratory studies have shown that schistosome worms can develop resistance to praziquantel and low cure rates from mass drug administration programs suggest that resistance is evolving in the field. Previous studies have identified thioredoxin glutathione reductase (TGR), a selenoprotein, as essential for schistosome survival, and therefore, a target for much-needed new therapeutics for sc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Given that praziquantel is the only effective treatment for schistosomiasis, there is an increasing concern that drug resistance may become more prevalent (Utzinger et al, 2009;Wang et al, 2012). More recently, pursuit of alternative antiparasitic drugs have been made possible by a more in-depth investigation of metabolic pathways specific to schistosomes and by direct study of TGR (Silvestri et al, 2018;Fata et al, 2021;Petukhova et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Given that praziquantel is the only effective treatment for schistosomiasis, there is an increasing concern that drug resistance may become more prevalent (Utzinger et al, 2009;Wang et al, 2012). More recently, pursuit of alternative antiparasitic drugs have been made possible by a more in-depth investigation of metabolic pathways specific to schistosomes and by direct study of TGR (Silvestri et al, 2018;Fata et al, 2021;Petukhova et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals this system is completely separated, in the other hand some invertebrate such as Flatworm and Schistosoma mansoni has encoded only one single gene, thioredoxin glutathione reductase (TGR) (Alger and Wiliams, 2002;Salinas et al, 2004;Otero et al, 2010). In the last 10 years this enzyme complex has received more attention, Ross et al, 2012;Petukhova et al, 2023 showed that thioredoxin glutathione reductase enzyme can be a potential target against these invertebrate animals.…”
Section: Immunometabolic Aspects Of Pentose Phosphate Pathwaymentioning
confidence: 99%
“…Non-covalent inhibitors of SmTGR offer several advantages over covalent inhibitors, including reversibility, selectivity, reduced potential for toxicity, ease of optimization, and lower risk of drug resistance. These properties make them promising candidates for the development of novel therapeutic agents against schistosomiasis [ 32 ]. Therefore, a collection of compounds exhibiting phenotypic antischistosomal activities served as the initial foundation for devising inhibitors targeting SmTGR, presenting a logical and effective method for identifying promising candidate compounds with possible therapeutic benefits against schistosomiasis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%